1988
DOI: 10.3147/jsfp.23.77
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microflora of larval and juvenile stages in Japanese flounder(Paralichthys olivaceus).

Abstract: Investigations on the aerobic bacterial flora in the intestine of larval and juvenile stages in Japanese flounder (Paralichthys olivaceus) were carried out at two different fisheries stations. The bacterial flora of ambient water and feeds were also analyzed. The number of bacteria in the intestine of larvae measuring 10 mm in total length was 105 CFU/fish, remained nearly constant until 14 mm, and decreased to 104 CFU/fish in 15-19 mm. The decrease in bacterial numbers was hypothesized to be due to the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 13 publications
(3 reference statements)
6
39
0
1
Order By: Relevance
“…from the results in several studies, environmental microflora markedly influence surface and some times intestinal microflora (Nieto et al, 1984;Camp bell and Buswell, 1983;Tanasomwang and Muroga, 1988;Cahill, 1990). However, this trend of relation ship was hardly achieved in this study as in the results obtained by Yoshimizu and Kimura (1976) when genus Vibrio formed as the dominant species in the intestines of salmonids cultured in seawater.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…from the results in several studies, environmental microflora markedly influence surface and some times intestinal microflora (Nieto et al, 1984;Camp bell and Buswell, 1983;Tanasomwang and Muroga, 1988;Cahill, 1990). However, this trend of relation ship was hardly achieved in this study as in the results obtained by Yoshimizu and Kimura (1976) when genus Vibrio formed as the dominant species in the intestines of salmonids cultured in seawater.…”
Section: Discussionmentioning
confidence: 98%
“…To elucidate pathogenesis of these bacterial pathogens and assess the role of gastro intestinal microflora in several marine finfishes, intestinal microflora of larval and juvenile stages were investigated (Yoshimizu and Kimura, 1976;Muroga et al, 1987;Tanasomwang and Muroga, 1988). Results obtained varied each other showing that intestinal flora were influenced mainly by flora of food ingested and/or flora of the environment.…”
mentioning
confidence: 99%
“…lensis and P. olivaceus (Tanasomwang & Muroga, 1988;Martin-Antonio et al, 2007). However, it is necessary to consider that the absence of Vibrio in WF may be due to (i) low dominance of this genus in the intestinal community, caused by the presence of bacteria with antagonistic effect against vibrios (Sun et al, 2009) or (ii) Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…The study also revealed that the total vibrio loads of water and rotifers were very high in C. calcitrans fed tanks, followed by tanks fed with combined diet N. occulata and I.galbana. It was observed that the diversity of the bacterial flora of rotifers is dependent on the flora of the rearing water [7] and V. alginolyticus was recorded as the most dominant microflora of rotifers, which produce a fatal exotoxin for B. plicatilis [8]. In contrary, V. anguillarum isolated and identified as the major dominant species in rotifer cultures but there was no record of mortalities due to this species [8].…”
Section: Application Of Probioticsmentioning
confidence: 99%